2015
DOI: 10.1590/1983-21252015v28n327rc
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade De Cebola Em Função De Doses De Nitrogênio E Épocas De Plantio

Abstract: RESUMO: A classificação da cebola realizadas com base no diâmetro dos bulbos e a qualidade medida pelos sólidos solúveis, acidez titulável, a pungência em função de doses de nitrogênio foi avaliada em dois experimentos conduzidos no período de dezembro de 2011 a abril de 2012 e de agosto a dezembro de 2012, na Horta do Departamento de Ciências Vegetais da Universidade Federal Rural do Semi-Árida em Mossoró-RN. O delineamento experimental utilizado foi em blocos casualizados completo com seis tratamentos e quat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
0
9
0
6
Order By: Relevance
“…Trani, Breda Júnior and Factor (2014) mentioned that the highest yield from onion was obtained with the N rate of 200 kg ha -1 , which is higher than that used in our experiment (173 kg ha -1 N). The application of 135 kg ha -1 N promoted higher percentages of bulbs in class-3 onions (RODRIGUES et al, 2015). These authors also recommend up to 160 kg ha -1 K 2 O, which is lower than the quantity accumulated by the onion plants in the current study (188 kg ha -1 K 2 O).…”
Section: Resultsmentioning
confidence: 46%
“…Trani, Breda Júnior and Factor (2014) mentioned that the highest yield from onion was obtained with the N rate of 200 kg ha -1 , which is higher than that used in our experiment (173 kg ha -1 N). The application of 135 kg ha -1 N promoted higher percentages of bulbs in class-3 onions (RODRIGUES et al, 2015). These authors also recommend up to 160 kg ha -1 K 2 O, which is lower than the quantity accumulated by the onion plants in the current study (188 kg ha -1 K 2 O).…”
Section: Resultsmentioning
confidence: 46%
“…Different results were observed by Bolandnazar et al (2012), Rodrigues et al (2016) and Benti (2017), who identified reduction of SS with the increase in N doses.…”
Section: Resultsmentioning
confidence: 67%
“…In onion, the absorption of nitrogen is surpassed only by that of potassium (Pôrto et al, 2007), and it is the nutrient that most affects bulb yield, health and quality (Resende et al, 2008). However, excessive quantity may limit bulb yield and increase post-harvest losses (Souza & Resende, 2002), whereas its deficiency may reduce bulb growth rate (Rodrigues et al, 2015).…”
Section: Introductionmentioning
confidence: 99%